Improving the Competence of Human Resources for the Development of Micro, Small, and Medium Enterprises (MSMEs) in Medan City which is mediated by the use of Information Technology - Sun Siagian, Tomy; Agusty Ningrum, Dhea (Publisher Cv. Inara, 2022)
The research is purposed to test and analyzed whether human resources affect UKMK development in Medan city by using information technology as an intervening variable. the kind of research is using the associative approach. The population of the research is an MSME user in Medan city divided into kinds of business, fashion, furniture, education, agriculture, fishery, healthy and automotive. There is the determination of the amount of the sample to use with the census method based on Stratify Random Sampling definition and the sample obtainable is 100. This research consists of the independent variable being the competency of human resources, the dependent variable being UMKM development, and an intervening variable being the user of information technology. the analysis of this research is using descriptive method. Structural Equation Modeling Analyzed based on variance (Partial Least Square). The result of the research are: (1) there are effects between human resource competency and UMKM development. (2) there are effects between information technology users and MSME development. (3) there are effects between human resource competency and information technology users. (4) there are effects between human resource competency and MSME development with mediated information technology users.